Quantification of exhaled propofol is not feasible during single‐lung ventilation using double‐lumen tubes: A multicenter prospective observational trial. Issue 4 (27th January 2023) - Hüppe, Tobias; Kreuer, Sascha; Wulf, Hinnerk; Freitag, Dennik; Seidel, Martin; Teucke, Tobias; Maurer, Felix; Kirschbaum, Andreas; Koch, Tilo; Langer, Frank; Volk, Thomas; Feldmann, Carsten
Abstract: Background: Volatile propofol can be measured in exhaled air and correlates to plasma concentrations with a time delay. However, the effect of single‐lung ventilation on exhaled propofol is unclear. Therefore, our goal was to evaluate exhaled propofol concentrations during single‐lung compared to double‐lung ventilation using double‐lumen tubes. Methods: In a first step, we quantified adhesion of volatile propofol to the inner surface of double‐lumen tubes during double‐ and single‐lumen ventilation in vitro. In a second step, we enrolled 30 patients scheduled for lung surgery in two study centers. Anesthesia was provided with propofol and remifentanil. We utilized left‐sided double‐lumen tubes to separately ventilate each lung. Exhaled propofol concentrations were measured at 1‐min intervals and plasma for propofol analyses was sampled every 20 min. To eliminate the influence of dosing on volatile propofol concentration, exhalation rate was normalized to plasma concentration. Results: In‐vitro ventilation of double‐lumen tubes resulted in increasing propofol concentrations at the distal end of the tube over time. In vitro clamping the bronchial lumen led to an even more pronounced increase (Δ AUC +62%) in propofol gas concentration over time. Normalized propofol exhalation during lung surgery was 31% higher during single‐lung compared to double‐lung ventilation. Conclusion: During single‐lung ventilation, propofol concentration in exhaled air, in contrast to our expectations, increased by approximately one third. However, this observation might not be affected by change in perfusion‐ventilation during single‐lung ventilation but rather arises from reduced propofol absorption on the inner surface area of the double‐lumen tube. Thus, it is only possible to utilize exhaled propofol concentration to a limited extent during single‐lung ventilation. Registration of Clinical Trial: DRKS‐ID DRKS00014788 (www.drks.de ).